A tough travesía: Mobility constraints among late Holocene Patagonian hunter-gatherers through oxygen stable isotopes in enamel and water sources. (October 2020) - Serna, Alejandro; Salazar-García, Domingo C.; Valenzuela, Luciano O.; Prates, Luciano
Highlights: The travesía creates a severe environmental fragmentation in North Patagonia. δ 18 O was used to infer the impact of the travesía in human mobility. Mobility trends suggest weak connectivity between areas separated by the travesía . The travesía functioned as a marginal space and influenced human circulation. Abstract: Central-eastern North Patagonia is characterized by a severe environmental fragmentation due to the scarce and heterogeneous distribution of fresh water. The main local wet zones, the Negro and Colorado river valleys in the North and the Somuncurá Foothills in the South are separated by a large and harsh dry land, the travesía . In this paper, we assess the effects of this environmental fragmentation in the mobility of the Late Holocene hunter-gatherers through the analysis of the stable isotopes of oxygen in both enamel and water sources. We analyzed the δ 18 O of the enamel carbonate of 64 human teeth from 42 individuals from the Negro River valley ( n  = 30) and the Somuncurá Foothills ( n  = 12) and transformed them into drinking water values (δ 18 Odw ) to be compared with an oxygen water baseline built from the most important surface water sources of the area. Our results show variable mobility, but they also highlight two trends regarding the direction of the movement. First, people buried at the Negro River valley seem to have consumed more regularly water from the Colorado River in the North than from other water sources located farther south (e.g. Somuncurá Foothills). Second, the δ 18 Odw values from the Somuncurá sample show east-to-west prevalent mobility along the foothills, far from the northern water sources (e.g. Colorado River). This weak connectivity between the northern and the southern parts of the study area (Negro and Colorado river valleys and Somuncurá Foothills) is probably related to the harsh environmental constraints imposed by the travesía . Our isotopic results in conjunction with the available archaeological and ethnohistorical data indicate that this large dry land acted as a marginal space in terms of human exploitation and that it certainly influenced human mobility.